CORRECTION OF CLASSIC DANCE MOVEMENTS BASE OF TECHNICAL BODY IN RHYTHMIC GYMNASTICS - Iorga Anca (Universitaria Publishing House, Craiova, 2017)
The in-depth knowledge of the mechanisms of execution of the movements is scientifically determinant in achieving sporting performance. In the training of gymnasts a special place is the choreographic training, which is mostly done through classical dance studies. Objectives of the study: The following objectives were assign: to improve the teaching system of body techniques in rhythmic gymnastics, to allow the extension of the technical training volume and to stop the early capping of gymnasts and to observe the possible biological influences of the dance studies classic gymnasts. Materioal and methods: The present paper aims at creating a methodical line, grouping the basic elements of body technique from a methodological point of view, evolutionary by age groups. Discussions and conclusions: Choreographic training of gymnasts can influence the compositional value of competitive exercises both at the artistic value level and at the level of the technical value. Classical dance through its progressive work forms and strengthens the deep muscles of the body, supporting the skeleton and the joints. By supporting the muscles of the support, the ligaments are also supported in their effort to resist the forces of gravity, compensatory movements can be avoided, as are the deformations of the different body segments. The correctness with which movements from the classical dance technique are made is the basis of a correct body technique in the world of rhythmic gymnastics.